The Effect of Product Variation and Sales Service on Customer Loyalty with Customer Satisfaction as A Mediating Variable: Case Study: JEL Classification: M31, L81, D12, C12, C51 - A Rahmat Hidayatulloh; Ida Rosnidah; Jefry Romdonny (Journal La Bisecoman, 2026)
The growth of the building materials retail industry in Indonesia, driven by rapid infrastructure development, has increased competition among businesses. This situation requires building materials stores to focus not only on product availability but also on service quality to create customer satisfaction and loyalty. This study aims to analyze the effect of product variety and sales service on customer loyalty, with customer satisfaction as a mediating variable at TB. Rahmat Jaya Mandiri in Cirebon Regency. This study used a quantitative approach with a survey method of 129 customer respondents. Data were analyzed using inferential statistical analysis techniques to test the direct and indirect effects between variables. The results showed that product variety and sales service did not have a significant direct effect on customer loyalty. In addition, product variety and sales service also did not have a significant effect on customer satisfaction. Testing the indirect effect showed that customer satisfaction was unable to mediate the effect of product variety or sales service on customer loyalty. The main finding of this study revealed that the only significant relationship was between customer satisfaction and customer loyalty, making customer satisfaction a key factor in the formation of loyalty. The results of this study indicate that in building materials stores, customers place more emphasis on functional aspects and reliability than product variety and emotional service. This research is expected to provide strategic considerations for building materials store managers in formulating policies to improve customer satisfaction and loyalty.